PENGARUH LITERASI DIGITAL DAN MOTIVASI PRESTASI TERHADAP HASIL BELAJAR EKONOMI PESERTA DIDIK DI SMA - Tairas, Anna; Basri, Muhammad; Syamsuri, Syamsuri (Jurnal Pendidikan Ekonomi (JURKAMI), 2024)
The low learning outcomes of students during learning activities are due to a lack of digital literacy and achievement motivation among students. In the current learning process that has been replaced with a digital system, we can take advantage of developments in technology and information and the importance of internal factors for students to be motivated to achieve. The aim of this research is to analyze the influence of digital literacy and achievement motivation on student learning outcomes in high school. The research approach is quantitative research with causal methods. The research sample was 88 students in class XI IIS of SMA Negeri 1 Nanga Taman. Data collection methods use questionnaires and test questions. Data were analyzed using multiple linear regression. The research results show: 1) digital literacy has a significant effect on the economic learning outcomes of students in high school with a sig value of 0.018 < 0.05. 2) achievement motivation has a significant effect on students' economic learning outcomes in high school with a sig value of 0.000 < 0.05. 3) digital literacy and achievement motivation simultaneously have a significant effect on students' economic learning outcomes in high school with a sig value of 0.000 < 0.05.